Comparación de rendimiento en seis variedades de cebada (Hordeum vulgare), forrajera y maltera, con dos densidades de siembra, aplicado a la industria cervecera, en la localidad de Laguacoto II, cantón Guaranda, provincia Bolívar - Manzano Baño, Carolina Jazmin (2022)
Barley cultivation worldwide is among the five most important foods along with corn, wheat, rice and potatoes. The Barley Value Chain (CVC) is mainly oriented to the production of grain for the large brewing and forage industry. In the Andean Zone and in the highlands of Ecuador, barley is an important part of the production systems of small producers to contribute to food security with various sub products such as the production of flour (Máchica), rice of barley and fodder for feeding cattle and minor species. In the province of Bolívar there is great potential for barley cultivation, particularly in the high zone in rotation after the potato and in the middle zone with legumes. The main limitations of barley cultivation in Ecuador are the low efficiency of cultivation systems due to the use of varieties susceptible to the complex of foliar diseases, seed of poor quality and deterioration of natural resources such as soil and climate change. This research was carried out at the Laguacoto Experimental Farm of the State University of Bolívar at an altitude of 2640 m.s.n.m. and in a clay loam soil. The objectives were: i) Validate the main agronomic characteristics of six varieties of fodder and malt barley, ii) Measure the effect of two planting densities on barley yield and iii) Perform the Economic Analysis of Partial Budget (EAPB) and Marginal Rate of Return (MRT%). For the implementation of the trial, the mathematical model of Design of Random Complete Blocs (DRCB) was applied in a factorial arrangement and with three repetitions. Factor “A” corresponded to six varieties of barley (Palmira, Alpha, Andreia, Guaranga, Cañicapa and Metcalfe) and Factor “B" to two planting densities (100 and 135 kg/ha). The main agronomic variables were evaluated in the field, postharvest and in the laboratory. The corresponding statistical analysis of variance, 5% Tukey test for barley varieties and interaction of factors, linear trend and main effect for planting densities, correlation analysis, linear regression, EAPB and MRT were carried out. Very different statistical differences were determined for most agronomic variables, especially as the main effect of the varieties. The highest average yields were determined in the INIAP Palmira and Alpha accessions with 6358 and 5640 kg/ha respectively. The sowing densities did not significantly affect the results, however with the sowing density of 135 kg / ha, the yield was increased by 8.6%. In the interaction of variety factors by planting densities statistically the best technological options were the treatments T2: A1B2 (INIAP Palmira with 135 kg / ha) and T1: A1B1 (INIAP Palmira with 100 kg / ha) with 6419 and 6296 kg / ha at 13% humidity. However, economically and taking into account only the costs that varied in each treatment wereT3: A2B1 (Alpha Variety with 100 kg / ha) and T1: A1B1 (INIAP Palmira with 100 kg / ha) with very similar MRT values of 498% and 497%. The most important effect was the varietal especially for the better agronomic behavior in terms of earlier crop cycle, tolerance to the main foliar diseases and better grain quality. Finally, this research allowed to select varieties with agronomic potential, grain quality and resilient to climate change for the agroecological zone of Laguacoto and contribute to crop diversification and food security.